Advances in the Function and Regulation of Hydrogenase in the Cyanobacterium Synechocystis PCC6803 - Cassier-Chauvat, Corinne (Int J Mol Sci, 2014)
In order to use cyanobacteria for the biological production of hydrogen, it is important to thoroughly study the function and the regulation of the hydrogen-production machine in order to better understand its role in the global cell metabolism and identify bottlenecks limiting H(2) production. Most of the recent advances in our understanding of the bidirectional [Ni-Fe] hydrogenase (Hox) came from investigations performed in the widely-used model cyanobacterium Synechocystis PCC6803 where Hox is the sole enzyme capable of combining electrons with protons to produce H(2) under specific conditions. Recent findings suggested that the Hox enzyme can receive electrons from not only NAD(P)H as usually shown, but also, or even preferentially, from ferredoxin. Furthermore, plasmid-encoded functions and glutathionylation (the formation of a mixed-disulfide between the cysteines residues of a protein and the cysteine residue of glutathione) are proposed as possible new players in the function and regulation of hydrogen production.